Czym jest sprawozdanie z działalności w roku obrotowym? - Kwiecień, Mirosława (What is financial statement for the financial year?, 2008)
The author has given the answer to the question of the essence of Financial statement for the financial year. According to the author, this statement is the most important part of financial reporting, necessary for the decision making process for stakeholders.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1199, s. 60-64